Teleoperation of Mecanum Wheels Robot Actuation Integrated with MQTT as an Interactive STEM Learning Tool - Rohman, Ardianto Syaifur; Genarsih, Tunjung; Dwianto, Sihmaulana; Afianah, Nuzula; Putri, Salsabila Liandra; Rofi’i, Ahmad; Purnomo, Fendik Eko; Kautsar, Syamsiar; Nari, Mochamad Irwan; Fanani, Nurul Zainal; Dwinanda, Angga (International Journal of Technology, Food and Agriculture, 2026)
This research presents the development of a teleoperation system for a mecanum wheel robot actuation integrated with the MQTT (Message Queuing Telemetry Transport) protocol to be used as an interactive STEM (Science, Technology, Engineering, and Mathematics) learning tool. The system employs four independently actuated mecanum wheels enabling omnidirectional mobility through coordinated wheel control. The teleoperation architecture utilizes a Raspberry Pi 3B+ connected to HiveMQ Cloud broker implementing MQTT protocol for real-time remote actuation via Flutter-based mobile interface. Each wheel actuation is controlled through L298N motor drivers operating at 300Hz PWM (Pulse Width Modulation) frequency, providing precise speed and directional control. Experimental results demonstrate system reliability with an average position deviation of 1.86 cm for forward actuation, 1.93 cm for backward, 2.64 cm for left slide, and 1.71 cm for right slide movements across 140 cm distance. The MQTT integration achieves a command execution latency of 200-400ms, suitable for educational teleoperation applications. The Flutter interface provides intuitive control with real-time visualization of wheel actuation states, enhancing user understanding of mecanum wheel kinematics. This implementation successfully demonstrates the effective use of teleoperation of a mecanum wheel robot actuation as platform for interactive STEM education, providing hands-on experience in robotics actuation, IoT protocols, control systems, and mobile application development.